Dynamic compaction of human mesenchymal stem/precursor cells (MSC) into spheres self-activates caspase-dependent IL1 signaling to enhance secretion of modulators of inflammation and immunity (PGE2, TSG6 and STC1) - Bartosh, Thomas J. (2013)
Human mesenchymal stem/precursor cells (MSC) are similar to some other stem/progenitor cells in that they compact into spheres when cultured in hanging drops or on non-adherent surfaces. Assembly of MSC into spheres alters many of their properties, including enhanced secretion of factors that mediate inflammatory and immune responses. Here we demonstrated that MSC spontaneously aggregated into sphere-like structures after injection into a subcutaneous air pouch or the peritoneum of mice. The structures were similar to MSC spheres formed in cultures demonstrated by the increased expression of genes for inflammation-modulating factors TSG6, STC1, and COX2, a key enzyme in production of PGE2. To identify the signaling pathways involved, hanging drop cultures were used to follow the time-dependent changes in the cells as they compacted into spheres. Among the genes up-regulated were genes for the stress-activated signaling pathway for IL1α/β, and the contact-dependent signaling pathway for Notch. An inhibitor of caspases reduced the up-regulation of IL1A/B expression, and inhibitors of IL1 signaling decreased production of PGE2, TSG6 and STC1. Also, inhibition of IL1A/B expression and secretion of PGE2 negated the anti-inflammatory effects of MSC spheres on stimulated macrophages. Experiments with γ-secretase inhibitors suggested that Notch signaling was also required for production of PGE2 but not TSG6 or STC1. The results indicated that assembly of MSC into spheres triggers caspase-dependent IL1 signaling and the secretion of modulators of inflammation and immunity. Similar aggregation in vivo may account for some of the effects observed with administration of the cells in animal models.